Reticular Corneal Edema or Corneal Honeycombing in Eyes Treated With Netarsudil: A Case Series. Issue 7 (July 2020) - Moumneh, Khaled; Sheybani, Arsham; Fellman, Ronald L.; Godfrey, David G.; Grover, Davinder S.
Abstract : This is a descriptive case series of 3 patients with uncontrolled intraocular pressure that developed reticular corneal changes after initiating netarsudil (0.02%). In all cases, upon observing reticular corneal edema, netarsudil (0.02%) was stopped followed by disappearance of corneal honeycombing. With the increasing use of this novel glaucoma medication, potentially more rare side effects will be observed. Reticular corneal edema or corneal honeycombing is an ocular examination finding that can rarely occur after initiating netarsudil (0.02%) regardless of prior corneal edema status. In our experience, the reticular changes resolve upon cessation of netarsudil.